An enhancement on electrochemical properties of Li+ ions battery-based PMMA/PLA-LiBOB gel polymer electrolytes - Nurhasniza, Mamajan Khan; Mohd Zieauddin, Kufian; Ahmad Salihin, Samsudin (Springer, 2024)
In the present work, the effect of SiO2 nanofiller on the electrochemical properties of GPEs prepared from PMMA/PLA has been discussed in detail. Two different systems are examined: PMMA/PLA-LiBOB (System I) and PMMA/PLA-LiBOB-SiO2 (System II). The Cole–Cole plots illustrate a notable reduction in bulk resistance consequent to the incorporation of SiO2, which results in a substantial improvement in ionic conductivity from 1.69 × 10–6 S cm−1 to 1.37 × 10–3 S cm−1 at ambient temperature, with the peak conductivity identified at 6 wt.% SiO2. The dielectric analysis reveals that SiO2 markedly augmented both the dielectric constant and dielectric loss, attributable to its elevated polarizability and the contributions from space charge polarization. Linear Sweep Voltammetry (LSV) measurements indicate voltage stability of 4.1 V for System I and 4.7 V for System II. Electrochemical performance comparisons demonstrate that System II outperforms System I in terms of stability and cycling performance, with differential capacity analysis further confirming the positive impact of SiO2 nanofiller on electrochemical activity.